Liss Peningkatan Protokol Kesehatan Covid-19 Di Tpq Al Amin Ngijo Wetan, Tasikmadu, Karanganyar - Liss Dyah; Erma Nurhayati Firdaus (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Washing hands with soap can prevent various infectious diseases, one of which is COVID-19. Fingers can be an entry point for viruses that can cause COVID-19 disease, therefore hand washing is one of the effective and efficient prevention efforts to avoid the occurrence of Covid-19 infection. This stimulus community service activity was carried out at TPQ Al Amin Ngijo Wetan, Tasikmadu, Karanganyar with 60 students with the aim of knowing the description of clean and healthy living behavior in the TPQ. From the results of observations, it was found that many of these students did not fully understand health problems and did not carry out the disciplinary behavior of washing hands with soap. This can be seen from the indicator that students' hands that look dirty are used directly to eat the food they buy without washing their hands first, even though before they played around and used the dirty hands to hold the face area. Therefore, this community service activity is carried out to provide understanding to students so that they are able to improve the behavior of washing hands with soap regularly. The method used in this community service activity is counseling, video screening, training, monitoring and evaluation. It is hoped that this research can increase awareness and have a positive impact and can actually be carried out by TPQ students.